Created in the Image? Holocaust Perpetrators in Israeli Fiction - Rogovin, Or (My University, 2013)
This dissertation studies aesthetic, political and ethical dimensions of the representation of Holocaust perpetrators in Hebrew and Israeli fiction published since the mid-1940s. Drawing on recent scholarship by Holocaust historians, such as Christopher Browning and Daniel Goldhagen, and on classical and post-classical theorists of narrative, such as E. M. Forster, Wayne Booth, and James Phelan, I examine modes, models, and possibilities applied in the treatment of Nazis, Nazi collaborators, and Germans in this fiction. My dissertation demonstrates that in Hebrew and Israeli fiction published before the mid-1970s, the dominant - but not exclusive - mode of characterization renders Holocaust perpetrators as relatively simple, stereotypical, and marginal characters. In contrast, as of the mid-1980s, the dominant mode of perpetrator characterization in Israeli fiction renders Nazis and Germans as significantly more complex, nuanced, and central characters, and the conventional boundary between them and their Jewish victims is blurred. These observations are based on a comprehensive survey of the major Hebrew and Israeli texts responding to the Holocaust, and more specifically on Ka-Tzetnik's Salamandra as a case study of earlier writing, and on David Grossman's See Under: Love and A. B. Yehoshua's Mr. Mani as case studies of recent fiction. As I show in detail, these contrasting literary approaches towards the perpetrators correspond to developments in other venues of Israeli public discourse, such as political speeches, journalism, and textbooks. My discussion also explores various ethical commitments and implications involved in the aesthetic and mimetic choices this fiction makes in its treatment of evil, as well as evaluating accomplishments and future developments in Israeli literary construction of the perpetrators. Although focused on Israeli fiction, the principles of inquiry utilized in my dissertation may contribute to understanding how other literatures respond to the Holocaust. Furthermore, my study can promote our understanding not only of how Israel perceives the Holocaust, but also how it perceives itself.
Thesis (Ph.D.)--University of Washington, 2012
Keywords: Evil; Holocaust; Israel; Nazi; Perpetrator; Victimizer; Literature; Judaic studies; Comparative literature